Product-service systems and supply chain circularity: a mixed methods investigation. - Kuhl, Carl-Christian (Cranfield University, 2021)
The circular economy (CE) aims to create economic and environmental benefits, by keeping products and materials at highest utility and value through long-lasting design, repair, reuse, refurbishment, and recycling. CE transformation results in a slowing, closing, and narrowing of resource loops, which is also termed supply chain circularity (SCC). Product-service systems (PSSs), in which manufacturers meet customer needs by providing services instead of selling products, are considered key business model innovations for increasing SCC. However, there is a lack of empirical evidence on whether PSSs actually contribute to SCC or whether they are a facade behind which linear ‘business-as-usual’ continues. This PhD thesis conducts a mixed methods investigation of the relationship between PSSs and SCC. It consists of three papers: 1) a systematic literature review (SLR) of 67 papers; 2) a quantitative survey of 206 machinery and equipment manufacturing firms in the United Kingdom (UK); 3) a multiple-case study of three manufacturing firms in Germany and the UK. The findings show that: 1) result-oriented PSSs have the highest potential contribution to SCC, followed by use- and finally product-oriented PSSs; 2) use-oriented PSSs are limited in contributing to a slowing of resource loops through refurbishment; 3) PSSs’ contribution to SCC depends on enabling and inhibiting contextual factors, especially organisational ones. In sum, this PhD study argues that PSSs can only catalyse the transition from a linear to a CE if an enabling business context is established. The PhD makes three key contributions to theory and practice: 1) it provides empirical evidence that PSSs do not inherently contribute to a slowing of resource loops; 2) it develops an empirically validated framework of enablers and barriers, particularly organisational ones; 3) it extends the SCC concept, by developing survey items and offering a first attempt at theorising how the transition to SCC occurs during a manufacturer’s servitization process.
Keywords: Circular economy; product-service system; supply chain management; servitization; case study; partial least squares structural equation modelling (PLS-SEM)